DOGMA TRITUNGGAL MENURUT KRISTEN SAKSI-SAKSI YEHUWA - Roni Ismail (UIN Sunan Kalijaga Yogyakarta, 2017)
In the tradition of mainstream Christianity, the Trinity is a very central dogma as a faith in God as the Father, the Son, and the Holy Spirit. It can be seen in the 12 creeds of the Apostolic Creed where the faith of the Trinity was first, second, and third. There is one school of Christianity, calling themselves Jehovah's Witnesses, rejecting the dogma of the Trinity in their divine concept. According to Jehovah's Witnesses, the word Trinity is not originated of the Bible. The Trinity is also not taught by early Christian Fathers and Pre-Nicene. The Trinity Dogma was introduced by Constantine for some reasons, and even continued in the Athanasian Creed. Jehovah's Witnesses therefore believe that the Trinity dogma is an apostate that the Bible has foretold, and is influenced by ancient beliefs and Platonism.